Method for producing positive electrode for lithium secondary battery, positive electrode produced using the same, and lithium secondary battery including the same
Patent Information
- Application Number
- JP2023544392
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-21
- Filing Date
- 2022-10-28
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-10-28
AI Technical Summary
【0028】 本発明により製造した正極を使用した場合、電極活物質層と電極集電体との間の接着力が高いため、二次電池の組立工程中に発生する活物質の脱離による容量減少および微細ショートなどの不良発生が抑制される効果がある。
Smart Images

Figure 0007640177000001
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority from Korean Patent Application No. 10-2021-0146518 dated October 29, 2021 and Korean Patent Application No. 10-2022-0136064 dated October 21, 2022.
[0002] The present invention relates to a method for producing a positive electrode for a lithium secondary battery containing a positive electrode active material of a lithium iron phosphate compound, a positive electrode for a lithium secondary battery produced using the same, and a lithium secondary battery containing the positive electrode. [Background technology]
[0003] As technological development and demand for mobile devices increases, the demand for secondary batteries as an energy source is rapidly increasing. Lithium transition metal composite oxides are used as the positive electrode active material of lithium secondary batteries, and among them, lithium cobalt composite metal oxides, which have high working voltage and excellent capacity characteristics, are mainly used. However, lithium cobalt composite metal oxides have low stability and are expensive, which makes it difficult to mass-produce lithium secondary batteries.
[0004] Therefore, lithium manganese composite metal oxides, lithium nickel composite metal oxides, lithium iron phosphate compounds, etc. have been developed as materials to replace the lithium cobalt composite metal oxides. Among them, lithium iron phosphate compounds having an olivinic structure have a high volume density, generate a high potential, and have a high theoretical capacity of about 170 mAh / g. In addition, in the initial state, lithium iron phosphate compounds contain one Li per Fe atom that can be electrochemically undoped, so they are promising materials as positive electrode active materials for lithium secondary batteries. Furthermore, since lithium iron phosphate compounds contain iron, which is a resource-abundant and inexpensive material, they are less expensive than the above-mentioned lithium cobalt composite metal oxides, lithium manganese composite metal oxides, and lithium nickel composite metal oxides, and have the advantage of being less toxic and less environmentally polluting.
[0005] However, lithium iron phosphate compounds have a limit in that the lithium insertion / extraction rate during charging / discharging is low, and therefore are manufactured with smaller particle sizes than positive electrode active materials of other compositions. When the particle size of the positive electrode active material is small, there is a problem that the adhesive strength with the current collector is low, and the positive electrode active material layer may be detached due to mechanical impact applied to the electrode during the secondary battery assembly process. When the positive electrode active material layer is detached, there are problems that the actually measured capacity of the secondary battery is reduced compared to the design capacity, and micro-short circuit defects occur due to the detached particles.
[0006] In the past, to solve these problems, techniques have been known to improve electrode adhesion by increasing the total binder content in the positive electrode active material layer, or by mitigating binder migration by increasing the drying time during electrode coating, thereby adjusting the binder content at the interface between the current collector and the active material layer to be high.
[0007] However, when the binder content in the active material layer is high, there is a drawback in that the resistance characteristics of the electrode and the energy density per volume of the electrode are reduced, and when the drying time is increased, there is a limit in that the production costs of the electrode and the secondary battery increase. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a method for manufacturing a positive electrode for a lithium secondary battery, which can increase the binder content in a positive electrode active material layer or increase electrode adhesion without increasing the drying time of the electrode when manufacturing a positive electrode including a lithium iron phosphate compound positive electrode active material having a small particle size.
[0009] Another object of the present invention is to provide a positive electrode produced by the above-mentioned production method, in which the electrode active material layer has excellent adhesion to the electrode current collector, and a lithium secondary battery including the above-mentioned positive electrode. [Means for solving the problem]
[0010] A method for producing a positive electrode for a secondary battery according to one embodiment of the present invention may include the steps of preparing a positive electrode in which a positive electrode active material layer containing a lithium iron phosphate compound is formed on a current collector, and allowing an organic solvent to be adsorbed onto the positive electrode active material layer.
[0011] In one embodiment of the present invention, the organic solvent may include one or more selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), isopropyl alcohol, acetone, and ethanol.
[0012] In one embodiment of the present invention, the organic solvent may include one or more selected from the group consisting of dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC).
[0013] In one embodiment of the present invention, the lithium iron phosphate compound may be a compound represented by the following formula 1:
[0014] [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b
[0015] In the above Chemical Formula 1, M includes any one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X includes any one or more elements selected from the group consisting of F, S, and N, and a, b, and x are -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively.
[0016] In one embodiment of the present invention, the lithium iron phosphate compound can be LiFePO4 with an olivine crystal structure.
[0017] In one embodiment of the present invention, the average particle size (D 50 ) may be 0.5 to 3 μm.
[0018] In an embodiment of the present invention, the positive electrode active material layer may further include a binder.
[0019] In one embodiment of the present invention, the binder may be one or more selected from the group consisting of polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC).
[0020] In one embodiment of the present invention, the binder content may be 5 wt % or less based on the total weight of the positive electrode active material layer.
[0021] In an embodiment of the present invention, the step of adsorbing the organic solvent to the positive electrode active material layer may include a process of directly spraying the organic solvent onto the positive electrode, or sealing the positive electrode together with the organic solvent in a sealed container to adsorb the organic solvent.
[0022] In one embodiment of the present invention, the organic solvent may be adsorbed at a ratio of 2,000 to 20,000 ppm based on the total weight of the positive electrode active material layer.
[0023] A positive electrode according to one embodiment of the present invention includes a positive electrode current collector, and a positive electrode active material layer formed on at least one surface of the positive electrode current collector and containing a lithium iron phosphate compound, and the positive electrode active material layer may contain 2,000 to 20,000 ppm of an organic solvent with respect to the total weight of the positive electrode active material layer.
[0024] In an embodiment of the present invention, the electrode adhesive strength measured in a 90° peel test between the positive electrode active material layer and a current collector may be 10 gf / 2 cm or more.
[0025] In one embodiment of the present invention, the positive electrode active material layer may be in direct contact with the positive electrode current collector.
[0026] In one embodiment of the present invention, the lithium iron phosphate compound has an average particle size (D 50 ) may be 0.5 to 3 μm.
[0027] The lithium secondary battery according to the present invention includes the above positive electrode. Effect of the Invention
[0028] When the positive electrode manufactured according to the present invention is used, the adhesive strength between the electrode active material layer and the electrode current collector is high, so that the occurrence of defects such as capacity reduction and micro-short circuit caused by detachment of the active material during the assembly process of the secondary battery can be suppressed.
[0029] Specifically, in the present invention, an organic solvent that is easily adsorbed by the active material, binder, and current collector is used, and organic solvent molecules are positioned at the contact interface between the current collector and the active material layer, thereby increasing the adhesive strength by forming an attractive force between atoms / molecules.
[0030] In addition, the positive electrode according to the present invention exhibits sufficient electrode adhesion without increasing the binder content, thereby improving the resistance characteristics of the secondary battery and improving the flexibility of the electrode. Furthermore, since the positive electrode exhibits sufficient electrode adhesion without increasing the drying time during the production of the positive electrode, the production cost and production time of the secondary battery can be reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The terms and words used in this specification and the claims should not be interpreted limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts that match the technical ideas of the present invention based on the principle that the inventor can appropriately define the concepts of the terms in order to best describe his own invention.
[0032] As used herein, terms such as "comprise," "comprising," or "having" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.
[0033] In the present invention, the “particle size D n " means the particle size at n% of the volume cumulative distribution by particle size. That is, D 50 is the particle size at the 50% point of the volume cumulative distribution by particle size, and D 90 is the particle size at the 90% point of the volume cumulative distribution by particle size, D 10 is the particle size at 10% of the cumulative volume distribution by particle size. The above Dn can be measured using the laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500). When the particles pass through a laser beam, the difference in the diffraction pattern due to the particle size is measured to calculate the particle size distribution. D 10 , D 50 and D. 90 can be measured.
[0034] The present invention will now be described in further detail.
[0035] The method for producing a positive electrode for a lithium secondary battery of the present invention may include the steps of preparing a positive electrode in which a positive electrode active material layer containing a lithium iron phosphate compound is formed on a current collector, and allowing an organic solvent to be adsorbed onto the positive electrode active material layer.
[0036] Specifically, the method for producing a positive electrode for a lithium secondary battery according to the present invention can prepare a positive electrode in which a composition for forming a positive electrode active material layer containing a lithium iron phosphate compound-based positive electrode active material is applied onto at least one surface of a positive electrode current collector, and then dried to form a positive electrode active material layer on the current collector.
[0037] The positive electrode active material layer forming composition can be produced by mixing or dispersing the positive electrode active material in a solvent.
[0038] The positive electrode active material may specifically include a lithium iron phosphate compound having a composition represented by the following formula 1, and more specifically, may include LiFePO4 having an olivine crystal structure. When the lithium iron phosphate compound is used as the positive electrode active material, it has the advantages of a high volume density of the positive electrode, a high potential, and a large capacity.
[0039] [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b
[0040] In the above Chemical Formula 1, M includes any one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, and X includes any one or more elements selected from the group consisting of F, S, and N, and -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5.
[0041] As a result of repeated efforts to improve the adhesive strength of a positive electrode containing the above-mentioned positive electrode active material, the inventors of the present invention discovered that the adhesive strength of the positive electrode can be dramatically increased by adding a step of adsorbing an organic solvent onto the positive electrode active material layer, and thus arrived at the present invention.
[0042] The organic solvent is not particularly limited as long as it can form an attractive force with the binder, the positive electrode active material, and the current collector contained in the positive electrode active material layer. Specifically, such an organic solvent is preferably an organic solvent used in a positive electrode slurry or an organic solvent used in an electrolyte of a lithium secondary battery.
[0043] Specific examples of the organic solvent used in the positive electrode slurry may include one or more selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), isopropyl alcohol, acetone, and ethanol.
[0044] The organic solvent used in the electrolyte of the lithium secondary battery is a non-aqueous organic solvent that serves as a medium through which ions related to the electrochemical reaction of the battery move. Specific examples of such organic solvents include ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone, ether-based solvents such as dibutyl ether and tetrahydrofuran, ketone-based solvents such as cyclohexanone, aromatic hydrocarbon-based solvents such as benzene and fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), and propylene carbonate. Examples of suitable solvents include carbonate solvents such as PC (carbonate), alcohol solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate solvents are preferred.
[0045] In the present invention, in order to increase the lithium insertion / extraction rate during charging / discharging of the lithium iron phosphate compound positive electrode active material, the average particle size (D 50 ) can be adjusted to 0.5 to 3 μm, preferably 0.5 to 2.7 μm, and more preferably 0.6 to 2.5 μm.
[0046] The positive electrode active material layer forming composition may further contain a binder in addition to the positive electrode active material.
[0047] The binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.
[0048] Among these, polyvinylidene fluoride (PVDF) is more advantageous than other binders in forming an intermolecular attractive force with the organic solvent of the present invention, and therefore polyvinylidene fluoride (PVDF) is preferred as the binder for the positive electrode of the present invention.
[0049] The binder may be contained in an amount of 5% by weight or less, preferably 1 to 5% by weight, and more preferably 2 to 3.5% by weight, based on the total weight of the solid content in the composition for forming a positive electrode active material layer. If the binder content is lower than the above range, there is a problem that the electrode adhesive strength is too low, and if the binder content is higher than the above range, there is a problem that the resistance of the secondary battery is too high.
[0050] The positive electrode active material layer forming composition of the present invention may further contain one or more additives such as a conductive material, a filler, or a dispersant.
[0051] The conductive material is used to improve the conductivity of the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the secondary battery.Specific examples include carbon powders such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, graphite powders such as natural graphite, artificial graphite, or graphite, conductive fibers such as carbon fibers, carbon nanotubes, and metal fibers, conductive powders such as carbon fluoride powder, aluminum powder, and nickel powder, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive materials such as polyphenylene derivatives, and one or more of these can be used alone or in mixture.
[0052] The conductive material may generally be contained in an amount of 0.3 to 5 wt %, preferably 0.3 to 4 wt %, and more preferably 0.5 to 3.5 wt %, based on the total weight of the solid content in the composition for forming a positive electrode active material layer.
[0053] The dispersant is for improving the dispersibility of the lithium iron phosphate-based positive electrode active material, and is not limited to any commonly used dispersant, for example, an aqueous dispersant or an organic dispersant may be used. Although not necessarily limited, hydrogenated nitrile rubber (HNBR) may be used more preferably. The hydrogenated nitrile rubber (HNBR) refers to a rubber obtained by subjecting nitrile butadiene rubber (NBR) to a hydrogenation reaction to convert the double bonds contained in the original nitrile butadiene rubber (NBR) into single bonds.
[0054] The dispersant may be contained in an amount of 0 to 4 wt %, preferably 0 to 2 wt %, and more preferably 0.10 to 1.3 wt %, based on the total weight of the solid content in the composition for forming a positive electrode active material layer.
[0055] In the production method of the present invention, the positive electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like may be used.
[0056] The positive electrode current collector may have a thickness of 8 to 20 μm, and may have fine irregularities on its surface to enhance adhesion to the positive electrode active material layer. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0057] In the manufacturing method of the present invention, the coating process of the composition for forming a positive electrode active material layer on the positive electrode current collector may be performed by a method commonly known in the art, such as uniformly dispersing the composition using a doctor blade, or by die casting, comma coating, screen printing, etc.
[0058] In the manufacturing method of the present invention, the composition for forming a positive electrode active material layer applied onto the positive electrode current collector can be dried according to a conventional drying method, for example, a vacuum heating treatment in the above-mentioned temperature range or a heat treatment method such as hot air injection.
[0059] At this time, the temperature of the drying process may be 60° C. to 130° C., specifically 80° C. to 130° C., and more specifically 100° C. to 130° C. At this time, when the temperature is within the above range, the moisture content in the lithium iron phosphate compound can be minimized, and volatile components contained during the process can be sufficiently removed, thereby preventing side reactions caused by these components and deterioration of battery characteristics during subsequent charging and discharging of the battery.
[0060] The time required for the drying step may be 5 minutes to 3 hours, specifically 5 minutes to 20 minutes, and more specifically 5 minutes to 10 minutes. When the production method according to the present invention is followed, the time required for the drying step can be shortened to the above range.
[0061] The method according to the present invention may further include a step of adsorbing an organic solvent to the positive electrode active material layer. The organic solvent is a material that is easily adsorbed to the active material, binder, and current collector, and the organic solvent molecules are positioned at the contact interface between the current collector and the active material layer, thereby increasing the electrode adhesive strength by forming an attractive force between atoms / molecules.
[0062] In one embodiment of the present invention, the organic solvent may be an organic solvent used in the positive electrode slurry, and specifically may include one or more selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), isopropyl alcohol, acetone, and ethanol.
[0063] In another embodiment of the present invention, the organic solvent may be an organic solvent constituting an electrolyte of a lithium secondary battery, and specifically may include one or more selected from the group consisting of dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC). The carbonate-based solvent has an excellent effect of improving adhesive strength.
[0064] When the organic solvent to be adsorbed on the positive electrode active material layer is selected to be the same as the organic solvent constituting the electrolyte of the secondary battery, there is an advantage in that a drying step for drying the organic solvent can be omitted after the organic solvent adsorption step.
[0065] In the manufacturing method of the present invention, the organic solvent can be adsorbed at a ratio of 2,000 to 20,000 ppm, preferably 2,000 to 10,000 ppm, and more preferably 2,000 to 4,000 ppm, based on the total weight of the positive electrode active material layer. If the adsorption amount is lower than the above range, the effect of improving the adhesive strength is limited, and if it is higher, there is a disadvantage that the adhesive strength with the separation membrane is reduced.
[0066] Specifically, the step of adsorbing the organic solvent to the positive electrode active material layer may be performed by directly spraying the organic solvent onto the positive electrode, or by sealing the positive electrode together with the organic solvent in a sealed container to adsorb the organic solvent.
[0067] When spraying the organic solvent with a spray nozzle, the concentration is 0.01 to 2 mg / cm 2 , preferably 0.01 to 1 mg / cm 2 , and more preferably 0.05 to 0.5 mg / cm 2 When the organic solvent is sprayed in the above amount, the organic solvent can be adsorbed in a suitable amount on the positive electrode active material layer. In addition, the positive electrode can be aged in a room temperature dry room environment so that the organic solvent applied to the surface is completely absorbed and impregnated into the inside of the electrode.
[0068] Alternatively, the petri dish containing the organic solvent and the positive electrode may be placed in a sealed container, sealed, and then stored for several days so that the organic solvent evaporated in the sealed container is adsorbed onto the positive electrode active material layer.
[0069] After the laminate of the positive electrode, negative electrode, and separator having the organic solvent adsorbed thereon is housed inside the exterior material of the battery, a process of drying the organic solvent may be performed before injecting the electrolyte in order to prevent a decrease in electrical characteristics due to the adsorbed organic solvent. However, when the organic solvent adsorbed on the positive electrode is the same as the electrolyte, the organic solvent adsorbed on the positive electrode may function as a medium for the movement of lithium ions, and therefore the drying process may be omitted.
[0070] The positive electrode produced according to the production method of the present invention contains an organic solvent in the positive electrode active material layer through a step of adsorbing the organic solvent. The content of the organic solvent in the positive electrode active material layer is 2,000 to 20,000 ppm based on the total weight of the positive electrode active material layer.
[0071] The content of the organic solvent may be defined as an average value calculated by measuring the amount of adsorption of the organic solvent three times using a headspace gas chromatography with flame ionization detection (HS-GC-FID) device for a positive electrode specimen obtained by cutting the positive electrode into a certain size.
[0072] When the organic solvent is an organic solvent used in a positive electrode slurry, such as NMP, the content of the organic solvent is preferably 2,000 to 12,000 ppm, 2,500 to 10,000 ppm, or 3,000 to 9,000 ppm.
[0073] When the organic solvent is an organic solvent used in the electrolytic solution, the content of the organic solvent may be 2,000 to 20,000 ppm, preferably 3,000 to 15,000 ppm, and more preferably 4,000 to 12,000 ppm.
[0074] In the positive electrode according to an embodiment of the present invention, the positive electrode active material layer is in direct contact with the positive electrode current collector, and may not include a separate layer for improving adhesion between the positive electrode active material layer and the positive electrode current collector.
[0075] The positive electrode according to the present invention contains the organic solvent in the positive electrode active material layer due to its unique manufacturing process, and the organic solvent forms an attractive force between the positive electrode active material and the current collector, thereby improving the adhesive strength at the contact interface between the positive electrode active material layer and the entire positive electrode collector. Therefore, the positive electrode according to the present invention can exhibit excellent adhesive strength, with an electrode adhesive strength of 10 gf / 2 cm or more, preferably 15 gf / 2 cm or more, measured in a 90° peel test, even without a separate layer, such as a binder layer, adhesive layer, binding layer, or primer coating layer, that may be interposed between the positive electrode current collector and the positive electrode active material layer to improve the adhesive strength.
[0076] As a result, the positive electrode of the present invention can improve the capacity and output characteristics of a battery due to increased adhesive strength, and can reduce defects that occur during the manufacturing process.
[0077] The present invention provides a lithium secondary battery including the above-mentioned positive electrode.
[0078] The lithium secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte, and the positive electrode is as described above.
[0079] In the lithium secondary battery, the negative electrode can be manufactured, for example, by preparing a negative electrode-forming composition containing a negative electrode active material and, optionally, additives such as a binder, a conductive material, a filler, and a dispersant on a negative electrode current collector, and then coating the composition on the negative electrode current collector.
[0080] In this case, the negative electrode active material is not particularly limited, and may be a compound capable of reversible intercalation and deintercalation of lithium.Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, and highly crystalline carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy, or composites containing metallic compounds and carbonaceous materials. In addition, examples of low crystalline carbon include soft carbon and hard carbon, and examples of high crystalline carbon include natural graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. One or a mixture of two or more of these may be used, and a metallic lithium thin film may also be used as the negative electrode active material.
[0081] The additives such as the binder, conductive material, filler and dispersant may be the same as those previously described for the positive electrode.
[0082] Meanwhile, the negative electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like, aluminum-cadmium alloy, etc. may be used.
[0083] In addition, the negative electrode current collector may typically have a thickness of 3 to 500 μm, and like the positive electrode current collector, the surface of the positive electrode current collector may be provided with fine irregularities to enhance the binding force of the negative electrode active material. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0084] Meanwhile, in the lithium secondary battery, the separator can be used without any particular limitation as long as it is one that is usually used as a separator in a lithium secondary battery, and in particular, it is preferable that the separator has low resistance to ion migration of the electrolyte and excellent moisture absorption ability of the electrolyte solution. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. can also be used. In addition, the separator can be a porous thin film having a pore diameter of 0.01 μm to 10 μm and a thickness of 5 μm to 300 μm.
[0085] The electrolyte may contain an organic solvent and a lithium salt that are commonly used in electrolytes, and is not particularly limited.
[0086] The organic solvent may be any organic solvent without particular limitation, so long as it can function as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, examples of the organic solvent that can be used include ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone, ether-based solvents such as dibutyl ether and tetrahydrofuran, ketone-based solvents such as cyclohexanone, aromatic hydrocarbon-based solvents such as benzene and fluorobenzene, and carbonate-based solvents such as dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC).
[0087] Among these, carbonate-based solvents are preferred, and mixtures of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of the battery, and low-viscosity linear carbonate-based compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) are more preferred.
[0088] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably contained in the electrolyte at a concentration of about 0.6 mol% to 2 mol%.
[0089] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.
[0090] The lithium secondary battery of the present invention may be manufactured by forming an electrode assembly by disposing a separator between a positive electrode and a negative electrode, and inserting the electrode assembly into a cylindrical or prismatic battery case and then injecting an electrolyte into the battery case. Alternatively, the electrode assemblies may be stacked, impregnated with an electrolyte, and then inserted into a battery case and sealed.
[0091] When manufacturing the lithium secondary battery of the present invention, the electrode assembly may be dried to remove one or more organic solvents selected from the group consisting of N-methyl-2-pyrrolidone (NMP), acetone, ethanol, propylene carbonate, ethyl methyl carbonate, ethylene carbonate, and dimethyl carbonate, which are used in manufacturing the positive electrode.
[0092] If an electrolyte having the same composition as the organic solvent used in the preparation of the positive electrode is used, the step of drying the electrode assembly can be omitted.
[0093] The battery case may be one commonly used in the art, and the shape of the battery case is not limited depending on the application of the battery. For example, the battery case may be a cylindrical shape using a can, a square shape, a pouch shape, or a coin shape.
[0094] The lithium secondary battery according to the present invention stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs).
[0095] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention may be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein.
[0096] <Example 1> Average particle size (D 50 A positive electrode active material of LiFePO4 with a particle size of 2 μm, a carbon nanotube conductive material, a polyvinylidene fluoride (PVDF) binder, and a hydrogenated nitrile rubber (HNBR) dispersant were mixed in a weight ratio of 95.4:0.8:3.0:0.8 (solid content 60 wt%) in N-methylpyrrolidone solvent to prepare a composition for forming a positive electrode. The discharge specific capacity of the final positive electrode formed on an aluminum thin film with a thickness of 15 μm was 2.9 mAh / cm. 2 The positive electrode was manufactured by rolling the positive electrode active material layer to a thickness of 96 μm using a roll press. In order to reduce the moisture content of the manufactured positive electrode, the positive electrode was vacuum dried at 130° C. for 10 hours.
[0097] Next, propylene carbonate (PC) solvent was sprayed onto the surface of the positive electrode active material layer of the positive electrode prepared above at a rate of 0.1 mg / cm using a spray nozzle. 2 The positive electrode was aged for 15 minutes in a room temperature dry room environment so that the propylene carbonate (PC) applied to the surface was completely absorbed and impregnated into the inside of the electrode.
[0098] When the PC dispersed by the spray nozzle was completely adsorbed onto the positive electrode without volatilization, the amount of PC adsorbed onto the entire active material layer was 4,000 ppm.
[0099] <Example 2> A positive electrode was prepared in the same manner as in Example 1, except that acetone was used as the coating solvent.
[0100] <Example 3> Average particle size (D 50 A positive electrode active material of LiFePO4 with a particle size of 2 μm, a carbon nanotube conductive material, a polyvinylidene fluoride (PVDF) binder, and a hydrogenated nitrile rubber (HNBR) dispersant were mixed in a weight ratio of 95.4:0.8:3.0:0.8 (solid content 60 wt%) in N-methylpyrrolidone solvent to prepare a composition for forming a positive electrode. The discharge specific capacity of the final positive electrode formed on an aluminum thin film with a thickness of 15 μm was 2.9 mAh / cm. 2 The positive electrode was manufactured by rolling the positive electrode active material layer to a thickness of 96 μm using a roll press. In order to reduce the moisture content of the manufactured positive electrode, the positive electrode was vacuum dried at 130° C. for 10 hours.
[0101] Next, the prepared positive electrode and the Petri dish containing N-methylpyrrolidone (NMP) solvent were placed in an airtight container, sealed, and stored for one day so that the NMP solvent evaporated in the airtight container was adsorbed on the positive electrode active material layer.
[0102] The positive electrode of Example 3 was prepared to a size of 50 mm × 50 mm, and the amount of adsorption of the NMP solvent was measured three times using HS-GC-FID (Headspace Gas Chromatography with flame ionization detection) equipment. The average value was calculated to be 2,600 ppm with respect to the entire positive electrode active material layer.
[0103] <Example 4> A positive electrode was prepared in the same manner as in Example 3, except that the prepared positive electrode and a Petri dish containing N-methylpyrrolidone (NMP) solvent were placed in an airtight container, sealed, and then stored for 5 days.
[0104] The positive electrode of Example 4 was prepared to a size of 50 mm × 50 mm, and the amount of adsorption of the NMP solvent was measured three times using HS-GC-FID (Headspace Gas Chromatography with flame ionization detection) equipment. The average value was calculated to be 8,600 ppm with respect to the entire positive electrode active material layer.
[0105] <Example 5> A positive electrode was prepared in the same manner as in Example 1, except that dimethyl carbonate was used as the coating solvent.
[0106] <Comparative Example 1> Average particle size (D 50 A positive electrode active material of LiFePO4 with a particle size of 2μm, a carbon nanotube conductive material, a polyvinylidene fluoride (PVDF) binder, and a hydrogenated nitrile rubber (HNBR) dispersant were mixed in a weight ratio of 95.4:0.8:3.0:0.8 (solid content 60% by weight) in N-methylpyrrolidone solvent to prepare a composition for forming a positive electrode, which was then uniformly coated on a 15μm-thick aluminum thin film so that the thickness of the positive electrode active material layer in the final positive electrode was 96μm to prepare a positive electrode. In order to reduce the moisture content of the prepared positive electrode, it was vacuum dried at 130℃ for 10 hours.
[0107] The positive electrode of Comparative Example 1 was prepared to a size of 50 mm × 50 mm, and the amount of adsorption of the NMP solvent was measured three times using HS-GC-FID (Headspace Gas Chromatography with flame ionization detection) equipment. The average value was calculated to be 160 ppm with respect to the entire positive electrode active material layer.
[0108] <Comparative Example 2> A positive electrode was prepared in the same manner as in Example 1, except that distilled water was used as the coating solvent.
[0109] The positive electrode of Comparative Example 1 was prepared to a size of 50 mm x 50 mm, and the amount of water adsorbed was measured three times using a Karl Fischer titration moisture meter (Metrohm). The average value was calculated to be 9,500 ppm for the entire positive electrode active material layer.
[0110] [Experimental example: Adhesion strength evaluation] The adhesive strength between the positive electrode active material layer and the positive electrode current collector was compared for the positive electrodes produced in the above Examples 1 to 5 and Comparative Examples 1 and 2.
[0111] Specifically, the positive electrodes prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were cut to a size of 150 mm long and 20 mm wide, and the electrode surface was attached to a glass slide of 75 mm long and 25 mm wide in the longitudinal direction using double-sided tape. That is, the glass slide was attached to an area corresponding to half of the positive electrode in the longitudinal direction. Then, a roller with a load of 2 kg was rubbed 10 times to uniformly attach the double-sided tape to prepare an evaluation sample. The glass slide portion of the evaluation sample was fixed to the sample stage of a Universal Testing Machine (UTM) (LF Plus, manufactured by LLOYD), and the half of the positive electrode to which the glass slide was not attached was connected to the load cell of the UTM equipment. The load cell was moved up to 50 mm at a speed of 100 mm / min, and the load applied to the load cell was measured. At this time, the minimum value of the load measured in the 20 mm to 40 mm section of the travel section was measured as the electrode adhesive force (gf / 2 cm) of each sample. Each positive electrode was evaluated five times in total, and the average values are shown in Table 1 below.
[0112] [Table 1]
[0113] As a result of the experiment, the positive electrodes of Examples 1 to 5 showed significantly higher adhesive strength than the positive electrodes of Comparative Examples 1 and 2. In the case of Comparative Example 1, it can be confirmed that the electrode adhesive strength was poor because, unlike the present invention, no organic solvent was adsorbed on the positive electrode active material layer. It is interpreted that the distilled water of Comparative Example 2 has a low intermolecular attraction with the PVDF binder, which is a binder with a relatively low polarity, and therefore has a low electrode adhesive strength effect.
Claims
1. preparing a positive electrode having a positive electrode active material layer including a lithium iron phosphate compound formed on a current collector; The positive electrode active material layer includes a step of adsorbing an organic solvent, The organic solvent includes one or more selected from the group consisting of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethyl methyl carbonate, ethylene carbonate, and propylene carbonate.
2. The lithium iron phosphate compound is a compound of the following formula 1: [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b 2. The method of claim 1, wherein, in Formula 1, M is one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y; X is one or more elements selected from the group consisting of F, S, and N; and a, b, and x are in the ranges of -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively.
3. The lithium iron phosphate compound is LiFePO having an olivine crystal structure. 4 The method for producing a positive electrode for a lithium secondary battery according to claim 1,
4. The average particle size (D 50 2. The method for producing a positive electrode for a lithium secondary battery according to claim 1, wherein the thickness of the first electrode is 0.5 to 3 μm.
5. The method for producing a positive electrode for a lithium secondary battery according to claim 1 , wherein the positive electrode active material layer further comprises a binder.
6. 6. The method for producing a positive electrode for a lithium secondary battery according to claim 5, wherein the binder is one or more selected from the group consisting of polyvinylidene fluoride, styrene butadiene rubber, and carboxymethyl cellulose.
7. 6. The method for producing a positive electrode for a lithium secondary battery according to claim 5, wherein the binder content is 5% by weight or less based on the total weight of the positive electrode active material layer.
8. 2. The method for producing a positive electrode for a lithium secondary battery according to claim 1, wherein the step of adsorbing the organic solvent to the positive electrode active material layer comprises directly spraying the organic solvent onto the positive electrode, or sealing the positive electrode together with the organic solvent in a sealed container to adsorb the organic solvent.
9. 2. The method for producing a positive electrode for a lithium secondary battery according to claim 1, wherein the organic solvent is adsorbed at a ratio of 2,000 to 20,000 ppm based on the total weight of the positive electrode active material layer.
10. a positive electrode current collector; and a positive electrode active material layer formed on at least one surface of the positive electrode current collector and including a lithium iron phosphate compound; The positive electrode for a lithium secondary battery, wherein the positive electrode active material layer contains 2,000 to 20,000 ppm of an organic solvent based on the total weight of the positive electrode active material layer.
11. 11. The positive electrode for a lithium secondary battery according to claim 10, wherein the electrode adhesive strength between the positive electrode active material layer and a current collector is 10 gf / 2 cm or more as measured in a 90° peel test.
12. The positive electrode for a lithium secondary battery according to claim 10 , wherein the positive electrode active material layer is in direct contact with the positive electrode current collector.
13. The average particle size (D 50 11. The positive electrode for a lithium secondary battery according to claim 10, wherein the average particle diameter is 0.5 to 3 μm.
14. A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to claim 10.
Citation Information
Patent Citations
Positive electrode for lithium ion secondary battery and manufacturing method thereof, and lithium ion secondary battery
JP2017027679A